Asymmetric architecture is non-random and repeatable in a bird's nests - Citizen Scientists (2022)
Bilateral, or left–right, asymmetry has evolved independently in many life forms and can be randomly, genetically or environmentally determined1. In a population, the frequency of left and right phenotypes can vary randomly or be fixed depending on, for example, their adaptive value1. Bilateral asymmetry has been described and quantified in individual morphological or behavioral traits, such as internal organ asymmetry or handedness1–3, but rarely in extended phenotypes. Bilateral asymmetry is present in animal architecture, such as snail shells or bird nests. How common and important asymmetry is in animal architecture remains to be quantified4. Here, we use a citizen-science approach to quantify the occurrence of left–right asymmetry in the complex nest of a bird, the rufous hornero (Furnarius rufus). We assess the possible evolutionary mechanisms underlying asymmetric nest architecture and predict a genetic underpinning.